Musikang Pinoyn ([Quezon City] The Institute)
Original Filipino music as expounded by its practitioners - Jim Paredes of APO Hiking Society, Freddie Aguilar and various bands and combos.
VHS
Host, Rowena Moran; editor, Jose Orbon
Keywords: Music -- Philippines; Music